Phonological development in children from 3 to 6 years in Quito - Acosta , Ruth (2021)
Introduction: Phonological development is an important component in the process of speech acquisition, that is why it is essential to evaluate its development through the percentage of phoneme, diphthong and consonant group mastery in preschool children to obtain information about the child's ability to articulate and correctly pronounce the sounds of language, it also serves to monitor the child's progress over time and adapt interventions and strategies for their treatment. Objective: To establish the percentage of mastery of phonemes, diphthongs and consonant groups in preschool children in the city of Quito. Material and methods: This is a cross-sectional descriptive epidemiological design study, in which 867 children between 3 and 6 years of age participated. After verifying that they met the selection criteria, they underwent a phonoaudiological clinical history, auditory evaluation, anthropometry, evaluation of the orophonatory organs, evaluation of orofacial praxias and articulation, and the Comprehensive and Expressive Language Exploration Test, Revised (ELCE-R), with the consent of their parents and school authorities. The study variables were analyzed using descriptive statistics. Results: The percentage of mastery of phonemes, diphthongs and consonant clusters was 95.07%. Conclusion: Children from 3 to 6 years of age living in Quito have a high level of phonological development, with mastery of phonemes, diphthongs and consonant clusters above the percentage expected for their chronological age, despite the fact that the test used is not contextualized to their linguistic reality.